HIV prevention is not all about HIV – using a discrete choice experiment among women to model how the uptake and effectiveness of HIV prevention products may also rely on pregnancy and STI protection - Vickerman, Peter (BMC Infect Dis, 2020)
INTRODUCTION: In sub-Saharan Africa, considerable HIV-burden exists among women. Anti-retroviral (ARV) based prevention products could decrease this burden, and their uptake could be increased if they also protect against pregnancy and sexually transmitted infections (STI). METHODS: A discrete choice experiment (DCE) was undertaken in South Africa (2015) through a household survey of adult females (n = 158) and adolescent girls (n = 204) who self-reported HIV-negative status. The DCE was used to project the uptake (percentage using product) of oral pre-exposure prophylaxis (PrEP), vaginal rings, and injectable long-lasting ARV agents among these women, and how uptake could depend on whether these products protect against pregnancy or STI acquisition. Uptake estimates were used to model how each product could decrease a women’s HIV acquisition risk. RESULTS: In adolescent women, there will be limited uptake (< 6% for any product) and impact (< 4% decrease in HIV acquisition risk) of new products unless they provide pregnancy protection, which could quadruple use and impact. Adult women have weaker preference for pregnancy protection, with moderate use (< 17% for each) and impact (< 14 percentage point decrease) if they only provide HIV protection. All women had highest preference for injectable ARVs, with oral PrEP having high preference if injectable ARVs are not available. Adult women will use the ring, but adolescent women will not. Importantly, even with three additional prevention products, all providing pregnancy and STI protection, > 14% of women will remain unprotected and > 31% of the baseline acquisition risk will remain. CONCLUSIONS: Incorporating multiple prevention components into new ARV-based prevention products may increase their uptake and impact among women.